Genome-wide transcriptional analysis of salinity stressed japonica and indica rice genotypes during panicle initiation stage - Walia, H.; Wilson, C.; Zeng, L.; Ismail, A.M.; Condamine, P.; Close, T.J. (Springer, 2007)
Rice yield is most sensitive to salinity stress imposed during the panicle initiation (PI) stage. In this study, we have focused on physiological and transcriptional responses of four rice genotypes exposed to salinity stress during PI. The genotypes selected included a pair of indicas (IR63731 and IR29) and a pair of japonica (Agami and M103) rice subspecies with contrasting salt tolerance. Physiological characterization showed that tolerant genotypes maintained a much lower shoot Na+ concentration relative to sensitive genotypes under salinity stress. Global gene expression analysis revealed a strikingly large number of genes which are induced by salinity stress in sensitive genotypes, IR29 and M103 relative to tolerant lines. We found 19 probe sets to be commonly induced in all four genotypes. We found several salinity modulated, ion homeostasis related genes from our analysis. We also studied the expression of SKC1, a cation transporter reported by others as a major source of variation in salt tolerance in rice. The transcript abundance of SKC1 did not change in response to salinity stress at PI stage in the shoot tissue of all four genotypes. However, we found the transcript abundance of SKC1 to be significantly higher in tolerant japonica Agami relative to sensitive japonica M103 under control and stressed conditions during PI stage.